MICELLER SOLUBILIZATION OF 1-NAPHTHOL BY SPECTROFLUORIMETRY - Jangir, Sunil Kumar; Acharya, Seema (Asian Journal of Pharmaceutical Research and Development, 2014)
1-Naphthol is widely used chemical in industry biomedical and forensic sciences. 1-naphthol is precursor to a variety of insecticides including carbaryl and pharmaceuticals nadolol. Micellar solubilization of 1-naphthol in nonionic and ionic surfactants heteromicroenvironment is monitored by fluorescence and absorption spectral techniques has been reported by the authors. The influence of surfactant, concentration and working experimental conditions on the fluorescence spectra of 1-naphthol is thoroughly evaluated and discussed. The increase in fluorescence intensity in micellar media can be attributed to the increase in quantum efficiency suggests that the suspended hydrophobic 1-naphthol molecules have been solubilized. The solubilizing action has been supplemented and confirmed by few theoretically calculated spectral parameters like, empirical fluorescence coefficient (kf ), quantum yield (φ f ), molar extinction coefficient (ε) and Stokes’ shift values.